Instructional leadership: The key to addressing psychological issues post-covid-19 - Dhandapani, Sudha; Kaur, Kamaljeet (Journal of Interdisciplinary Studies in Education, 2024)
In this paper, we examined the challenges school leaders faced during and after COVID-19, including maintaining teacher morale and student engagement. Utilizing bibliometric analysis, the study reveals instructional leadership as a crucial factor in addressing psychological issues. The findings demonstrate that shared instructional leadership by principals is essential for effective crisis management. This research highlights the importance of adaptive instructional leadership in navigating uncertainty. By adopting collaborative approaches, school leaders can mitigate the pandemic’s psychological impact, foster resilience, and promote a supportive learning environment.